Reading the Forum on China-Africa Cooperation (2000-2021): geoeconomics, governance, and embedding 'creative involvement' - Cheng, Han; Mawdsley, Emma; Liu, Weidong (Area development and policy, 2023)
How China can promote its overseas commercial and strategic interests and protect its citizens and investments while continuing to adhere to a longstanding commitment to non-interference is a subject of intense policy and academic debate. A notion of 'creative involvement' has been developed to specify an increasingly flexible and pragmatic approach to projecting and managing China's expanding global interests. In this research a close reading of the Declarations and Action Plans of the Forum on China-Africa Cooperation (FOCAC) over the period 2000-21 reveals specific degrees and types of embedding of Chinese involvement in Africa's complex political economic landscape and an evolving reorientation of development cooperation policy practices shaped by growing concerns with African economic policy and local governance issues.